The case for aromatase inhibitors use in Oncofertility patients. Should aromatase inhibitors be combined with gonadotropin treatment in Breast Cancer patients undergoing ovarian stimulation for fertility preservation prior to chemotherapy? A debate. (December 2013) - Fatum, Muhammad; McVeigh, Enda; Child, Tim
Abstract Breast cancer is one of the hormone-dependent cancers that may be adversely affected by elevated oestrogen or progesterone concentrations, particularly the endocrine active (hormone receptor positive) breast cancers. Treatment for breast cancer patients aimed at fertility preservation, includes ovarian hyperstimulation, the harvest of oocytes, and subsequent cryopreservation of oocytes or embryos. Classically, gonadotrophins have been used effectively for ovulation induction, a treatment often accompanied by high blood oestrogen concentrations produced by the hyperstimulated granulosa cells. Despite the uncertainty which surrounds this issue and the lack of clear-cut clinical evidence, it is still of major concern that these ensuing high hormone levels might be associated with a high risk of recurrence of the cancer. A growing number of clinical studies have strongly suggested the benefits of using aromatase inhibitors in infertility treatment, both as single agents or as adjuncts to FSH-containing ovulation induction regimes in reproductive medicine. Combining gonadotrophins with aromatase inhibitors would augment the stimulation effect, with a reduced increase in serum concentrations of estradiol. We propose to open a debate over the use of aromatase inhibitors in combination with FSH in ovulation induction treatment of breast cancer oncofertility patients. As the safety of aromatase inhibitors such as letrozole has recently been demonstrated in several studies, and there is growing concern over the possible detrimental effects of high estradiol levels on breast cancer cells (at least in mouse models), the co-administration of letrozole in these patients would reduce both the high supraphysiologic serum levels of estradiol and the intratumoral in situ production of oestrogen. However, since it is unlikely that a well-founded evidence-based justification of this treatment will be formulated in the near future, based on well-designed prospective randomised controlled trials, we advocate a wider use of aromatase inhibitors in combination with gonadotrophins in breast cancer patients, especially those with hormone-receptor-positive tumours.